(untitled) (Bangladesh Journal of Agricultural Research, 2012)
The impact of extension contact is examined with a view to evaluating the agriculture extension in Bangladesh. It is found that the impact of extension contact is stronger for the comparatively near villages to upazila headquarters. This effect is weaker for those villages, which are comparatively away from upazila headquarters. Evident shows that the influence of extension contact is strongly positive and significant in the upazila where people are mostly involved in agricultural works. The results show that the impact of extension contact, which is one of the basic tenet of agricultural extension, as found in the yield of rice in the whole survey area, is strongly positive and significant. Some determinants of extension contact are also examined. Findings revealed that education of farmers, size of farm families, number of earners of farm families, irrigation and villages which are nearer to the upazila headquarters are key determinants for a household participation in extension contact. DOI: http://dx.doi.org/10.3329/bjar.v36i4.11762 Bangladesh J. Agril. Res. 36(4): 723-732, December 2011